2013
DOI: 10.5539/ass.v9n15p253
|View full text |Cite
|
Sign up to set email alerts
|

The Millennium Development Goals (MDGs) and the Challenges of Youth Development in Nigeria

Abstract: Despite the adoption of the Millennium Development Goals (MDGs) in 2000, the Nigerian youth is still caught in a web of poverty, hopelessness and missed opportunities. The paper argues that though corruption, lack of political will, poor policy implementation, etc. limit government's efforts at youth development, the primary challenge remains the fact that the government has not been able to properly conceptualise and prioritize youth development. In addition, government's implementation of the Millennium Deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…On the other hand, any lack of ownership of the MDGs by national governments is widely cited as a major constraining factor for MDG implementation (Haug & Hella, 2013; Hulme & Scott, 2010; Ukachukwu & Iheriohanma, 2013). Scholars have shown that many governments of developing countries had little interest in the MDGs and were hence reluctant to translate global goals into national contexts (Fukuda‐Parr, 2014; Hezri, 2013).…”
Section: Results: Success Factors For the Implementation Of The Mdgsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, any lack of ownership of the MDGs by national governments is widely cited as a major constraining factor for MDG implementation (Haug & Hella, 2013; Hulme & Scott, 2010; Ukachukwu & Iheriohanma, 2013). Scholars have shown that many governments of developing countries had little interest in the MDGs and were hence reluctant to translate global goals into national contexts (Fukuda‐Parr, 2014; Hezri, 2013).…”
Section: Results: Success Factors For the Implementation Of The Mdgsmentioning
confidence: 99%
“…In particular, countries that suffer from socio‐economic inequality and lacking administrative capacity with deficient coordination are not able to take adequate measures that improve pro‐poor development (Asadullah & Savoia, 2018; Mashau et al, 2014), basic health services for the poor (Das, 2018), environmental protection (Castelló et al, 2010; Opršal et al, 2018) or other MDG targets (Comim, 2015; Haug & Hella, 2013; Hoxhaj et al, 2014; Sío‐López, 2015). Such capacity deficits open the door for policymakers to distort the programmes for their own gains leading to poor MDG implementation (Hezri, 2013; Omona, 2010; Ukachukwu & Iheriohanma, 2013). This is most evident in conflict zones and areas without statehood where the MDGs had essentially no effects (Caprani, 2016).…”
Section: Results: Success Factors For the Implementation Of The Mdgsmentioning
confidence: 99%